Design of DWT based Image Compression Technique for Wireless Sensor Network Applications - Tanasan, Prayoth; Srikotr, Kumsawat (International Journal of Engineering and Technology, 2018)
In this paper, we propose an efficient image compression strategy exploiting the multi-resolution characteristic of the wavelet transform. We use MATLAB simulation to evaluate the image compression technique called â€œDiscrete Wavelet Transform Skipped High Pass Sub-band (DWT-SHPS). Furthermore, we have implemented an image compression using DWT-SHPS technique on a low-cost single board computer. The evaluation is performed under the wavelet compression framework from the view point of quality of image and data compression ratio. Different combinations of parameters and transformation levels have been compared against the JPEG compression standard. The experimental results indicate that the SHPS technique is close to the performance of JPEG standard. It efficient and has low complexity with less memory requirements in the hardware implementation.Â Â